Detecting Insider Threat through Psychometric Scores and Work Environment - Yogi, Manas Kumar; Mundru, Yamuna (Journal of Soft Computing Paradigm, 2022)
Nowadays the cyber-threat is looming large from disgruntled employees rather than external attackers. With the advent of modern threat models which help in development of adversary attack scenarios, the security designers can get an idea of attack mitigation strategies. The analysis of threat model helps in knowing the unforeseen circumstances which can lead to a cyber-security risk. If the weakness in the network or in any other element of a cyber-ecosystem is identified during the design of security models, then eventually it will lead to stronger security applications. This paper formulates a framework of identification of insider threat which may be a result of various factors in an organization. The proposed technique considers psychometric condition of an employee along with other factors which may give rise as a threat to the organization. The dataset has been used to train the model and the experimental results have found an effective way to detect the insider threat in specific cases.